Low-dose onabotulinumtoxinA improves urinary symptoms in noncatheterizing patients with MS. (14th August 2018) - Tullman, Mark; Chartier-Kastler, Emmanuel; Kohan, Alfred; Keppenne, Veronique; Brucker, Benjamin M.; Egerdie, Blair; Mandle, Meryl; Nicandro, Jean Paul; Jenkins, Brenda; Denys, Pierre
Abstract : Objective: To evaluate the efficacy and safety of onabotulinumtoxinA 100 U in noncatheterizing patients with multiple sclerosis (MS) with urinary incontinence (UI) due to neurogenic detrusor overactivity (NDO). Methods: In this randomized, double-blind phase III study, patients received onabotulinumtoxinA 100 U (n = 66) or placebo (n = 78) as intradetrusor injections via cystoscopy. Assessments included changes from baseline in urinary symptoms, urodynamics, and Incontinence–Quality of Life (I-QOL) total score. Adverse events (AEs) were assessed, including initiation of clean intermittent catheterization (CIC) due to urinary retention. Results: OnabotulinumtoxinA vs placebo significantly reduced UI at week 6 (−3.3 episodes/day vs −1.1 episodes/day, p < 0.001; primary endpoint). Significantly greater proportions of onabotulinumtoxinA-treated patients achieved 100% UI reduction (53.0% vs 10.3%, p < 0.001). Significant improvements in urodynamics ( p < 0.01) were observed with onabotulinumtoxinA. Improvements in I-QOL score were significantly greater with onabotulinumtoxinA (40.4 vs 9.9, p < 0.001) and ≈3 times the minimally important difference (+11 points). The most common AE was urinary tract infection (25.8%). CIC rates were 15.2% for onabotulinumtoxinA and 2.6% for placebo. Conclusion: In noncatheterizing patients with MS, onabotulinumtoxinA 100 U significantly improved UI and quality of life with lower CIC rates than previously reported with onabotulinumtoxinA 200 U. ClinicalTrials.gov identifier: NCT01600716. Classification of evidence: This study provides Class I evidence that compared with placebo, 100 U onabotulinumtoxinA intradetrusor injections significantly reduce UI and improve quality of life in noncatheterizing patients with MS and NDO.